Depression and religiosity among urban elderly population of western Uttar Pradesh, India - Singh, Anshumali; Kaushal, S. K.; Misra, S. K.; Agrawal, Renu (International Journal Of Community Medicine And Public Health, 2018)
Background: India is a country with rich cultural and spiritual background. Research suggests that engagement in religious activity, or religiosity, may protect against depression. This cross-sectional study examines whether religiosity is associated with depression in elderly. The objectives of the study were to assess the presence of depression among elderly population of urban Agra and to find the association between religiosity and depression amongst urban elderly. Methods: This community based cross-sectional study was conducted on a sample of 355 community dwelling older adults residing in urban Agra. One municipal ward was randomly chosen, further three residential colony from the ward was randomly selected. All the houses of colonies were visited sequentially. One person, chosen randomly from eligible family members was invited to participate. After establishing rapport and obtaining written informed consent from participants, the information was recorded in a semi-structured, pre-designed and pre-tested questionnaire. Results: The mean age of the participants was 68.05 years with 52.96% males and 47.04% females. Overall, depression was found in 51.1% among study population. Depression was more among non-religious (60.61%) and among those who were not involved in any extrinsic or intrinsic religious activity. Conclusions: Findings suggest that both organizational and non-organizational forms of religiosity affect depression in the study group. Important strategies to prevent and relieve depression among older adults may include improving access and transportation to places of worship among those interested in attending services.